Tests of Fibrous and Nonfibrous Reinforced Concrete Continuous Deep Beams with Web Openings - Saeed, Jalal Ahmed; Yousif, Ali Ramadhan (Sulaimani Journal for Pure and Applied Sciences, 2013)
Test results of twenty four two-span reinforced concrete deep beams, with or without web openings and with or without steel fibers are reported. All test specimens had the same cross-section, main longitudinal top and bottom reinforcement, and web reinforcement. The main parameters considered were the shear span-to-total beam depth ratio (a/h), position of the web openings, and the amount of steel fibers. Test results indicated that the presence of web openings within exterior or interior shear spans had great effects on the beam capacity and its behavior, with the diagonal cracking between loads and supports being dominant. In these beams, the crack patterns revealed the fact that the contribution of the top reinforcement was not significant. However, the top reinforcement showed better contribution in solid beams and beams with openings within midspan region especially when the shear span-to-depth ratio was increased. The crack patterns were less affected by the addition of steel fibers, however, an increase in the ultimate load capacity was obtained. The amount of increase in the ultimate load was about 10% in solid beams and beams having openings within midspan region, while the amount of increase was dependent on the shear span/depth ratio and location of the openings in the other beams. Also the fibrous beams showed better degree of serviceability requirements.
Keywords: deep beams nonflexural members shear strength; web openings plasticity strutandtie models